FT‐IR characterization and hydrolysis of PLA‐PEG‐PLA based copolyester hydrogels with short PLA segments and a cytocompatibility study. Issue 24 (24th September 2013) - Wang, David K.; Varanasi, Srinivas; Fredericks, Peter M.; Hill, David J.T.; Symons, Anne L.; Whittaker, Andrew K.; Rasoul, Firas
ABSTRACT A series of the biodegradable copolyester hydrogels was prepared using a redox‐initiated polymerization with a constant 1:9 mole ratio of the Boltorn‐based acrylate and diacrylate triblock comacromonomers. The Boltorn® macromonomer was derived from the hyperbranched polyester Boltorn H20, which was functionalized at each terminus with poly(ethylene glycol) acrylate, and the diacrylate triblock macromonomer was poly (lactide‐b‐ethylene glycol‐b‐lactide) diacrylate. The hydrolysis of the copolyesters at pH 7.4 in a phosphate buffered saline solution at 37 °C was studied using ATR‐FTIR spectroscopy. It was found that the presence of the Boltorn, the PEG, and lactide block lengths both play vital roles in determining the structure‐property relationships in these materials. The ATR‐FTIR studies showed that with increasing lactide segment length, the rate of ester hydrolysis increased due to the increased concentration of the hydrolytically sensitive poly(lactic acid) (PLA) ester groups in the network. However, incorporation of Boltorn into the PLA‐PEG‐PLA copolymer did not significantly change the kinetic rate constant for hydrolysis of the PLA segments. The cytocompatibility of a typical one of these materials in the presence of its degradation by‐products was assessed using cultured osteoblasts from the rat. The hydrogel was degraded for 28 days and found to be cytocompatible with osteoblasts over days 23 to 28 of the hydrolysis period. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 5163–5176